GOVERNMENT ACCOUNTABILITY IN THE FINANCING OF K-12 EDUCATION IN ARGENTINA, BRAZIL, AND URUGUAY - Gil, Juca; Farias Machado, Maria Goreti; Farenzena, Nalú; Pinheiro Mosna, Rosa Maria (Jornal de Políticas Educacionais, 2022)
The paper contrasts the government accountability in the financing of K-12 education in Argentina, Brazil, and Uruguay. It describes the countries’ specificities in two periods with distinct government political lines: the 1990s, with the adoption of policies with a neoliberal matrix, and the period from 2000 to 2014, with the enactment of progressist policies for expansion of public expense in the three Latin American States. The topics presented in the comparative analysis represent the priorities of the state action regarding education, such as the right to it, compulsory and free education, public resources aimed to education, accountability between spheres and instances of government, and public expense. Each topic was analyzed in view of the situations of maintenance, redefinition, or partial redefinition concerning the two historical periods. The most usual situation in these countries was the redefinition of compulsory education, the change for higher in the references for expense in education, as well as renegotiations in the distribution of accountability between national and subnational governments in Argentina and Brazil.